Study on the Electrical Equivalent Circuit Model of Lightning Fault Cause in Power Grid System - Asman S.H.; Abidin A.A.Z.; Ngah N.A.R.M.; Aziz N.F.A.; Kadir M.Z.A.; Mustafa N.B.A.; Weng L.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Circuit simulation; Electric power transmission networks; Equivalent circuits; Lightning; Timing circuits; Digital fault recorder; Electrical equivalent circuit; Equivalent circuit model; Fault model; Grid systems; Lightning fault model; Lightning faults; Lightning strikes; Power grid system; Transmission-line; Electric lines